Analisis Kolokasi Verba Bahasa Inggris Berbasis Korpus Dalam Novel “Five Feet Apart” - Krisnawati, Krisnawati (Jurnal Ilmiah Multidisiplin Amsir, 2023)
This research aims to explain (1) the frequency of verb bases forming verb collocations in the novel "five apart", (2) the grammatical and lexical categories of verb collocations, (3) the construction of lexical category verb collocations, and (4) the function of verb collocations on sentence in the novel "five feet apart". This research data was taken from the novel by Lippincott, Mikki Daughtry, and Tobias Laconis in the form of collocations in the form of phrases and clauses. Data was collected by applying a corpus machine. The collected data was analyzed using Quirk's grammar theory and Palmer's semantic theory. The results of the analysis were presented using formal and informal methods. Based on the analysis carried out, it was found: that (1) there were four findings in this analysis. The verb base frequencies of the English verb collocations of the novel "five feet apart" from the application of corpus software were classified into three frequencies, medium and low frequencies. (2) The verb collocation categories found in the novel "five feet apart" are grammatical and lexical. (3) Syntactic construction of verb collocations that contain noun collocations are verb phrases and clauses. Meanwhile, verb collocation constructions that contain adverbial collocates are adverbial clauses and phrasal verbs. (4) The function of verb collocations in the sentences found is studied from the basis that forms phrases and clauses acting as subjects, predicates, and objects. Meanwhile, the collocation function is studied from the collocator's role as a fixed combination.